New insights into gibberellin signaling in regulating flowering in Arabidopsis - Bao, Shengjie; Hua, Changmei; Shen, Lisha; Yu, Hao (Journal of integrative plant biology, 2020)
In angiosperms, floral transition is a key developmental transition from the vegetative to reproductive growth, and requires precise regulation to maximize the reproductive success. A complex regulatory network governs this transition through integrating flowering pathways in response to multiple exogenous and endogenous cues. Phytohormones are essential for proper plant developmental regulation and have been extensively studied for their involvement in the floral transition. Among various phytohormones, gibberellin (GA) plays a major role in affecting flowering in the model plant Arabidopsis thaliana. The GA pathway interact with other flowering genetic pathways and phytohormone signaling pathways through either DELLA proteins or mediating GA homeostasis. In this review, we summarize the recent advances in understanding the mechanisms of DELLA‐mediated GA pathway in flowering time control in Arabidopsis, and discuss its possible link with other phytohormone pathways during the floral transition. Gibberellin (GA) is one of major plant hormones that affects flowering time in Arabidopsis. In this review, we summarized the recent advances in understanding the molecular mechanisms of DELLA‐mediated GA pathway in flowering time control in Arabidopsis, and discussed the possible links with other phytohormone pathwaysduring the floral transition.